Faktor Risiko Anemia pada Ibu Hamil Trimester Ketiga di Puskesmas Tanjung Sekayam: Studi Kasus-Kontrol: The Risk Factors for Anemia in Women at Third Trimester of Pregnancy in the Primary Health Center of Tanjung Sekayam: A Case-Control Study - Arfan, Iskandar; Marlenywati, Marlenywati; Saleh, Ismael; Rizky, Ayu; Marlina, Marlina (Amerta Nutrition, 2024)
Background: The presence of anemia in pregnant women significantly affects the health of both mothers and their fetuses. Around 37% of pregnant women worldwide experience anemia. In the Community Health Center of Tanjung Sekayam, the prevalence of anemia in women at the third trimester of their pregnancy was notably high, at 50.4%. Objectives: This study aims to identify the risk factors for anemia in women at third trimester of pregnancy in the working area of the Community Health Center of Tanjung Sekayam Subdistrict, Sanggau Regency. Methods: This study was an observational research with a case-control design. The study population consisted of 153 women at third trimester of pregnancy, receiving antenatal care in the Community Health Center of Tanjung Sekayam. The samples included 62 respondents, selected through a simple random sampling, comprising of 31 cases and 31 controls. Data were collected using questionnaires and analyzed with the Chi-Square test to assess the factors associated with the occurrence of anemia. Results: There was a relation among maternal age (p=0.000; OR=22.9), interpregnancy interval (p=0.024; OR=6.9), parity (p=0.011; OR=2.2), nutritional status (chronic energy deficiency) (p=0.000; OR=11.3), compliance (p=0.021; OR=3.9), and knowledge (p=0.001; OR=8.2) and the prevalence of anemia in the third trimester. However, the family support did not show any significant relation. Conclusions: Maternal age, pregnancy interval, parity, nutritional status, compliance with iron tablet intake, and knowledge are related to the prevalence of anemia in third trimester of pregnancy. Family support did not show any significant relation with the incidence of anemia, possibly due to the limitations in measuring the family support itself and other factors, such as discomfort in consuming iron tablets and forgetfulness. More structured interventions and intensive education on the importance of iron and nutrition during the pregnancy are needed to reduce the risk of anemia.